Implementasi Komunikasi Pemasaran dalam Menarik Minat Konsumen di Wall Street English - Bernadett, Fiona CH; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The need for English communication skills is increasing, learning institutions such as Wall Street English are here to bridge the gap between language and communication skills. Wall Street English is an international English course institution, founded in 1972 in Italy and has many branches in various countries, including in Indonesia. Communication and mastery of foreign languages, especially English, are two important elements in the era of globalization, English serves as an international language that allows the exchange of information. Effective communication is important to create a clear understanding of the value and advantages offered to potential customers. The research was conducted with a qualitative approach with a case study method, the research subject is the Assistant Brand Marketing Manager at Wall Street English and the object of research which is the research problem is marketing communication at Wall Street English in attracting consumer interest. This research shows that the marketing communication that has been done. Wall Street English in attracting consumer interest is applying the 7P marketing mix and applying marketing tools, namely advertising and personal selling. Thus, the effective implementation of marketing communication is not only an effort to attract consumers but also to attract customers. Kebutuhan akan kemampuan komunikasi bahasa inggris semakin meningkat, lembaga pembelajaran seperti Wall Street English hadir untuk menjembatani kesenjangan antara kemampuan bahasa dan komunikasi. Wall Street English adalah lembaga kursus Bahasa Inggris Internasional, didirikan pada tahun 1972 di Italia dan memiliki banyak cabang di berbagai negara, termasuk di Indonesia. Komunikasi dan penguasaan bahasa asing khususnya Bahasa Inggris merupakan dua elemen penting dalam era globalisasi, bahasa inggris berfungsi sebagai bahasa internasional yang memungkinkan pertukaran informasi. Komunikasi yang efektif menjadi penting untuk menciptakan pemahaman yang jelas tentang nilai dan keunggulan yang ditawarkan kepada calon konsumen. Penelitian dilaksanakan dengan pendekatan kualitatif dengan metode studi kasus, subjek penelitian merupakan Assistant Brand Marketing Manager di Wall Street English dan objek penelitian yang menjadi permasalahan penelitian merupakan komunikasi pemasaran di Wall Street English dalam menarik minat konsumen. Penelitian ini menunjukkan bahwa komunikasi pemasaran yang telah dilakukan. Wall Street English dalam menarik minat konsumen yaitu menerapkan marketing mix 7P serta menerapkan marketing tools yaitu advertising dan personal selling. Dengan demikian, penerapan komunikasi pemasaran secara efektif tidak hanya menjadi upaya untuk menarik konsumen tetapi juga menjadi kunci untuk mempertahankan posisi kompetitif dalam industri.